Large breathing effect in ZIF-65(Zn) with expansion and contraction of the SOD cage - Gao, Meizhen; Huang, Rui-Kang; Zheng, Bin; Wang, Pengfei; Shi, Qi; Zhang, Wei-Xiong; Dong, Jinxiang (Nature communications, 2022)
The flexibility and guest-responsive behavior of some metal-organic frameworks (MOFs) indicate their potential in the fields of sensors and molecular recognition. As a subfamily of MOFs, the flexible zeolitic imidazolate frameworks (ZIFs) typically feature a small displacive transition due to the rigid zeolite topology. Herein, an atypical reversible displacive transition (6.4 Å) is observed for the sodalite (SOD) cage in flexible ZIF-65(Zn), which represents an unusually large breathing effect compared to other ZIFs. ZIF-65(Zn) exhibits a stepwise II → III → I expansion between an unusual ellipsoidal SOD cage (8.6 Å × 15.9 Å for II) and a spherical SOD cage (15.0 Å for I). The breathing behavior of ZIF-65(Zn) varies depending on the nature of the guest molecules (polarity and shape). Computational simulations are employed to rationalize the differences in the breathing behavior depending on the structure of the ZIF-65(Zn) cage and the nature of the guest-associated host–guest and guest–guest interactions. Flexible metal-organic frameworks have potential applications in the development of sensors and switching materials. Here, the authors report a large breathing effect in a zeolitic imidazolate framework upon guest adsorption.